Efeitos de Regras que Relatam Justificativas Sobre o Comportamento de Seguir Regras - MATSUO, Gilsany Leão (Universidade Federal do Pará, 2019)
The present study investigated the effects of rules that provide justifications on the rule- following. 12 undergraduate students were exposed to a matching-to-sample procedure, The task consisted of pointing, in a sequence, to each of three comparison stimuli that had only one thing in common with the sample stimulus and differed in other characteristics. Participants were exposed to four experimental conditions that differed only as the order of presentation of the rules. Were presented to participants rules describing minimal justifications (JMI), monetary justification (JMO), social justification (JSO) and monetary justification more social justification (JMO + SO). The rules always describing two options for response, with different response cost: a greater response effort (EFCFCE) and another with less response effort (EFC). The rule with a minimal justification (JMI) had no justification for issuing any sequence. The other rules presented justifications for issuing a sequence of higher cost (EFCFCE). The results showed that 80% of the participants have chosen sequence higher cost (EFCFCE) when exposed to rules with justifications (JMO; JSO; JMO+SO). And 75% of participants chose sequence of lower cost (EFC) when exposed to rule with minimal justification (JMI). It is concluded that effects of rule-following is due, in part, to the formal properties of the rules.